Inkjet printing MoS2 nanosheets for hydrogen sensing applications - Han, Seung Ik; Yeasmin, Rubaya; Duy, Le Thai; Noh, Yong Gyu; Lee, Sang Yeon; Park, Chiwan; Jung, Gwanggyo; Kwon, Kye Si; Seo, Hyungtak (Journal of the Korean Ceramic Society, 2024)
2D nanomaterials are of great interest in many modern applications. In particular, MoS2 nanomaterial with a narrow band gap of 1.8 eV is expected as one of the best candidates for low-cost gas sensors. To reduce the costs of scalable sensor production, inkjet printing technology has attracted much attention during the current transition period of the fourth industry. Here we report an economical hydrogen-sensor using inkjet-printed MoS2 nanosheets with Pd nanocatalyst (MoS2–Pd). Few-layer MoS2 nanosheets were synthesized via a mechanical exfoliation method, and Pd nanodots (as an Irish type) were formed using short e-beam evaporation. Our fabricated sensors based on MoS2–Pd have a small channel area of 5 × 300 µm, enabling superfast response and recovery of the sensors (~ 6.6 s) toward a wide range of hydrogen concentrations at 50 °C. With the high sensing performance and endurability, our inkjet-printed sensor devices are promising for practical hydrogen sensing and storing applications, and our study shows a valuable route to develop gas-sensitive inks for other analytes.
Keywords: 2D nanomaterial; E beam evaporation; Hydrogen sensor; Hydrogen-sensing; Ink jet; Ink-jet printing; MoS2 nanosheet; Nanodots; Pd nanodot; Sensing applications; E-beam evaporation; Hydrogen sensor; Inkjet printing; MoS2 nanosheets; Pd nanodots